Recovery of LiCoO2 and graphite from spent lithium-ion batteries by cryogenic grinding and froth flotation - Liu, Jiangshan; Wang, Haifeng; Hu, Tingting; Bai, Xuejie; Wang, Shuai; Xie, Weining; Hao, Juan; He, Yaqun (Minerals engineering, 2020)
[Display omitted] •Binder wrapped on electrode particles weakens their surface properties.•Cryogenic grinding can remove the organic binder efficiently.•Removing organic binder can expose new surface of electrode particles.•Removing organic binder can eliminate agglomeration of electrode particles.•Electrode materials before and after cryogenic grinding are fully investigated. A novel method of cryogenic grinding and froth flotation is proposed to recover LiCoO2 and graphite from spent lithium-ion batteries. After 9 min of cryogenic grinding, the grade of LiCoO2 concentrate was up to 91.75%, with a recovery rate of 89.83% after flotation, but the materials that have not been cryogenic grinding, the grade and recovery rate of LiCoO2 after flotation only 55.36% and 72.8%, respectively. Analysis of the surface properties and morphology of electrode particles was performed using scanning electron microscopy, X-ray photoelectron spectroscopy, and field emission-electron probe micro-analysis. Results indicate that the organic binder on the surface of the raw materials resulted in a poor recovery rate and grade of the flotation concentrate. Cryogenic grinding, on the other hand, caused the organic binder on the surface of electrode materials to peel off, with spherical graphite changing into a scaly layer structure that revealed a new surface. The hydrophilicity of LiCoO2 and hydrophobicity of graphite were obviously improved by cryogenic grinding, and in turn contributed to an excellent flotation separation. This work provides an efficient and environmentally-friendly process for recovering LiCoO2 and graphite from spent lithium-ion batteries.